On the Pan Heights. - Unknown (Trinidad Guardian)
This year's bi-annual Steelband Music Festival displays the heights to which pan has risen. The festival is dedicated to Anthony Williams, pioneer leader of Pan Am North Stars, and businessman Ram Kirpalini, who helped revived the festival. Organization is needed for the steelband movement and individual bands to become economically self sufficiency as the era of massive sponsorship is drawing to a close.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago